The Professional versus the Amateur A Case Study on Spanish Female Detectives and Their Role in the Masculine and Machista Organizations on the Examples of Selected Texts - Tęcza, Agata (Romanica Silesiana)
In the present work, I wish to concentrate on two examples of detective fiction in Spain, that is on Arturo Pérez Reverte’s The Flanders Panel and Alicia Giménez Bartlett’s Serpientes en el paraíso. Both novels are centred on a character of a female detective. After a closer look, we can see that both detectives have found themselves in a similar situation. Julia, the amateur, and Petra, the professional, exist and work in a typically masculine world of detectives and police officers, struggling with the gender issues and roles. By analysing their situations, I wish to present a case study of two female detectives and their reactions, responses and attitudes towards the masculine world of sleuths, thus providing a complete picture of both protagonists. Key words: female detective fiction, machismo, Arturo Pérez Reverte, Alicia Giménez Bartlett, Petra Delicado.